Zur Toxizität des Fliegenpilzes (Amantia muscaria L.) für Diptera, insbesondere die Große Stubenfliege (Musca domestica L.). - Petzsch, Hans (Contributions to Entomology = Beiträge zur Entomologie, 1960)
The author discusses the use of the toadstool (Amantia muscaria L.) to control Musca domestica L. dealing with methods of application already in practice 100 years ago, and drawing the attention of modern insecticide research to the question wether some investigations to isolate the toxic factors of the fungus would present new outlooks on house fly control with regard to the increasing importance of the resistance problem.